Ekstraksi Tanin dari Limbah Kulit Biji Asam dan Penggunaannya Sebagai Biomordan pada Pewarnaan Tenun Timor Secara Alami - Risna Erni Yati Adu; Marselina Theresia Djue Tea; Yunita Bouk (Universitas Andalas, 2022)
Tannins from tamarind seed husk were extracted and applied as a biomordant for natural dyeing process of Timor woven fabrics. Tannins were extracted using hot distilled water, qualitatively and quantitatively analyzed and applied as a color binder to the woven fabrics. The color characteristics of woven fabrics with tannins were compared to the woven fabrics that mordanted with Al2(SO4)3 and FeSO4 at the concentration of 15%. Tamarind seed husk tannins are in the form of a brownish red powder. Qualitative and quantitative tests showed that tamarind seed coat contained condensed tannins with a total concentration of 70.08 ± 0.14%. Tannins identification by FT-IR spectroscopy showed a strong band absorption at 3369 cm-1 for O-H group and a weak absorption at 1721 cm-1 due to the C=O stretch. A strong absorption at 1611-1608 cm-1 was observed for C=C group in the aromatic ring and was strengthened with a strong absorption at 1520 cm-1, C-O-C group which is specific for condensed tannins was observed at 1285 cm-1. Application of 15% tannin as a biomordant without natural dye on Timor woven fabric produced a brownish red color, while the use of 15% tannin and turmeric dye showed a brownish yellow color. Tannin exhibited a better color fastness than metalic mordants in natural dyeing of Timor woven fabrics.